Real-world medication persistence and outcomes associated with basal insulin and glucagon-like peptide 1 receptor agonist free-dose combination therapy in patients with type 2 diabetes in the US - Lin J; Lingohr-Smith M; Fan T (Dove Medical Press, 2016)
Jay Lin,1 Melissa Lingohr-Smith,1 Tao Fan2 1Health Economics and Outcomes Research, Novosys Health, Green Brook, NJ, USA; 2North America Medical Affairs, Sanofi US, Inc., Bridgewater, NJ, USA Background: Free-dose combination treatment with basal insulin and short-acting glucagon-like peptide-1 receptor agonists (GLP-1 RAs) reduces hyperglycemia via complementary targeting of fasting and postprandial blood glucose levels, however, in the real world, due to injection burden and clinical inertia, the full efficacy may not be able to translate into clinical and economic benefits. Objective: The aim of the study was to evaluate treatment persistence and associated outcomes in patients with type 2 diabetes (T2D) treated with a GLP-1 RA in free-dose combination with basal insulin. Methods: Claims data were extracted on US adults with T2D with ≥1 prescription claim for both a GLP-1 RA and a basal insulin from July 1, 2008 to June 30, 2013, and continuous health plan coverage for 6 months prior to (baseline) and 12 months after the index date (follow-up period). Outcomes analyzed for patients stratified by treatment persistence included glycemic control, hypoglycemia, and health care costs and resource utilization. Multivariate analyses were used to examine factors associated with persistence or hypoglycemia. Results: The analysis included 7,320 patients, of whom 16.9% were persistent with free-dose combination treatment. The median time to treatment discontinuation was 133 days. Compared with nonpersistent patients, persistent patients had greater glycated hemoglobin A1c (A1C) reductions (–0.80% vs –0.42%; P=0.032), were more likely to achieve A1C <7.0% (39% vs 22%; P<0.001), and were less likely to experience hypoglycemia (9.5% vs 6.8%; P=0.002). Persistent patients also had significantly fewer hospitalizations and shorter hospital stays. While prescription costs were significantly higher (all-cause: $14,691 vs $10,791; P<0.001; diabetes-related: $8,142 vs $5,124; P<0.001), total medical charges were significantly lower (all-cause: $28,405 vs $40,292; P=0.001; diabetes-related: $11,114 vs $15,203; P=0.003) for persistent patients compared with nonpersistent patients. Conclusion: This retrospective claims study of US patients with T2D showed that, although persistence with concurrent GLP-1 RA and basal insulin treatment is low, improved treatment persistence is associated with greater A1C reductions and lower total medical charges. Keywords: basal insulin, GLP-1 receptor agonist, treatment persistence, type 2 diabetes